Análise e uso clínico de um novo equipamento que quantifica a deformidade das mãos em indivíduos com diabetes mellitus tipo 2 - Iwamoto, Helen Cristina Tiemi (2018)
INTRODUCTION: Diabetes Mellitus is a chronic metabolic disease and affects several systems, including the musculoskeletal system. Limited joint mobility (LJM) syndrome is a frequent manifestation evaluated by prayer sign and table top sign (TTS) tests to identify joint limitation of the fingers. The peripheral musculoskeletal impairment leads to reduced joint mobility and muscle strength which affects the functionality of the hand and daily activities. Thus, there is need for new elements to identify reliably and quantitatively musculoskeletal manifestations of hand. OBJECTIVE: To analyze whether the musculoskeletal manifestations of the fifth MCF in individuals with type 2 diabetes (T2D) can be evaluated using the Fontana’s Table Top Sign Analyzer(FTTSA) and evaluate the functionality of the hand using the Disabilities of the Arm, Shoulder and Hand (DASH). METHODS: Two studies were conducted and 55 individuals with DM2 were evaluated. In study 1 the evaluations were performed by two evaluators, blinded to each other, through the TTS and FTTSA tests. We used ICC analysis, 95% CI for reliability, Person for correlation analysis, Bland-Altman for intra and inter-examiners agreement, for predictive validity we used ROC curve and post-test analysis. In study 2, the individuals were evaluated by means of anamnesis, FTTSA, DASH questionnaire and handgrip strength (HGS). The Student-Mann-Whitney t-test and the Spearman or Person correlation were used for the comparison analyzes for the parametric or non-parametric variables, respectively. It was considered for all α 5% tests. RESULTS: Study 1 found that the inter-examiners analysis for right metacarpophalangeal (RMCP) showed good reliability (ICC = 0.61, p <0.0001), 95% CI 0.41-0.75, SEM 9.42, DMD 21.78, correlation (r = 0.61; p <0.0001), good agreement (bias -2.9). For left metacarpophalangeal (LMCP), there was reliability (ICC = 0.57, p <0.0001), 95% CI 0.37-0.73, EPM 11.22, DMD 25.94, correlation (r = 0.57, p <0.0001), good agreement (bias -2,4). Intra-examiner analyzes for RMCP (CCI = 0.38, p = 0.002) and LMCP (CCI = 0.47, p <0.0001) presented moderate reliability for RMCP correlation (r = 0.38, p = 0.004) and LMCP (r = 0.47, p = 0.0003), presence of agreement RMCP (bias -3.2) and LMCP (bias 2.2). The predictive validity established the presence of deformity (<583.83 a.u.) and absence (≥583,83 a.u.), sensitivity (78%) and specificity (64%). Post-test characteristics for RMCP and LMCP were, respectively: PPV = 68% and 50%, NPV = 75% and 68%, PLR = 2.2 and 1.9, and NLR = 0.4 and 0.9. In study 2, there was a correlation between HGS and total DASH score (r = -0.50; p <0.0001) and significant difference (p <0.0001) for DASH between the female and male sexes. There was no significant difference and association between the DASH questionnaire with the presence of deformity, age, diabetes time and glycemic control. CONCLUSION: Study 1 - The FTTSA equipment has good reliability, reproducibility and agreement, being more effective for the analysis of RMCP inter - examiners.The sensitivity, specificity and predictive values of RMCP indicate that the evaluation with the FTTSA equipment is a good diagnostic test to identify LJM. Study 2 - Individuals with T2D with greater impairment in hand functionality have lower handgrip strength and predominantly females.